2004
DOI: 10.1023/b:brea.0000032979.52773.fb
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Detection of Metastasized Breast Cancer Cells in the Lymph Node; Potential Application for Sentinel Lymphadenectomy

Abstract: Metastasis is the leading cause of death in breast cancer patients and an appropriate detection of metastasis can provide better prognosis and quality treatments. Microwaves can reveal the unique electromagnetic properties of materials, and this study aims to unleash the electromagnetic properties of breast cancer cells, especially, metastasized cancer cells in the lymph nodes, using broad-band microwaves in attempts to detect metastases. To distinguish the cancer-specific patterns of cancer tissues, three pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 22 publications
1
35
0
2
Order By: Relevance
“…Meaney et al also suggested that a correlation existed between the average permittivity values and the radiographic density of the tissue, since patients categorised radiographically as having high fat content tissue had an average permittivity value of 31, while patients categorised as having heterogeneously dense tissue (a) (b) Figure 4. The variation of (a) the relative permittivity, and (b) the conductivity of normal and malignant tissue between 0.5 GHz and 30 GHz as reported by Choi et al [35].…”
Section: Dielectric Properties Of Breast Tissuementioning
confidence: 87%
See 1 more Smart Citation
“…Meaney et al also suggested that a correlation existed between the average permittivity values and the radiographic density of the tissue, since patients categorised radiographically as having high fat content tissue had an average permittivity value of 31, while patients categorised as having heterogeneously dense tissue (a) (b) Figure 4. The variation of (a) the relative permittivity, and (b) the conductivity of normal and malignant tissue between 0.5 GHz and 30 GHz as reported by Choi et al [35].…”
Section: Dielectric Properties Of Breast Tissuementioning
confidence: 87%
“…Campbell and Land also noted much greater variance in the dielectric properties of normal tissue than suggested in previous studies. In a more recent study, Choi et al [35] measured the dielectric properties of breast cancer tissue, along with the properties of metastasised lymph nodes and normal lymph nodes in the frequency band between 0.5 and 30 GHz. The results of the measurements are shown in Figure 4, once again illustrating a dielectric contrast between normal and malignant breast tissue.…”
Section: Dielectric Properties Of Breast Tissuementioning
confidence: 99%
“…It should be noted that although lymph nodes are not constituents of the breast per se, they are represented in this figure as breast cancer can be diagnosed through detection of metastasised tumour cells particularly in the axillary lymph nodes, where approximately 50% of breast cancer occur [18,19]. …”
Section: Anatomy and Physiology Of The Breastmentioning
confidence: 99%
“…Knowledge of the complex permittivity in an treated area, i.e. knowledge of the complex permittivity of healthy and tumor tissue, is very important for example in the diagnosing of tumor regions in the human body (Choi et al, 2004) or in the design of thermo-therapeutic applicators which transform electromagnetic energy into thermal energy in the tissue (Williams et al, 2008). Permittivity is known as…”
Section: Complex Permittivitymentioning
confidence: 99%